Combining creatinine and volume kinetics identifies missed cases of acute kidney injury following cardiac arrest - Pickering, John W.; Md Ralib, Azrina; Endre, Zoltan H. (Critical Care Forum, 2013)
Introduction Fluid resuscitation in the critically ill often results in a positive fluid balance, potentially diluting the serum creatinine concentration and delaying diagnosis of acute kidney injury (AKI).